Locus-specific differential expression of human satellite sequences in the nuclei of cancer cells and heat-shocked cells - Christina Rabeler; Nicholas Paterna; Rajiv Potluri; Lia R. D’Alessandro; Anusha Bhatia; Shu Yi Chen; Johanna Lee; Bereketab Abeje; Benjamin Lipchin; Benjamin R Carone; Dawn M. Carone (Nucleus)
Human satellites (HSats) are pericentric, tandemly repeating satellite DNA sequences in the human genome. While silent in normal cells, a subset of HSat2 noncoding RNA is expressed and accumulates in the nucleus of cancer cells. We developed a FISH-based approach for identification of the distribution of three subfamilies of HSat2 (A1, A2, B) sequences on individual human chromosomes. Further, using the HSat subfamily annotations in the T2T completed centromere satellite (CenSat) sequence, we isolated, defined and mapped differentially expressed sequence variants of nuclear-restricted HSat2 and HSat3 RNA from cancer cell lines and heat-shocked cells. We identified chromosome-specific and subfamily-specific expression of HSat2 and HSat3 and established a computational pipeline for differential expression analysis of tandemly repeated satellite sequences. Results suggest the differential expression of chromosome-specific HSat2 arrays in the human genome may underlie their accumulation in cancer cells and that specific HSat3 loci are upregulated upon heat shock.